Silicone Leather
The silicone leather composite material, enhanced with a textile support, silicone binder, skin, and top coat layers, and a silicone/polyurethane hybrid coating, addresses wear resistance issues, enabling broader application in durable environments.
Patent Information
- Application Number
- JP2024533292
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-12-28
AI Technical Summary
Silicone leather composite materials suffer from inadequate mechanical strength and wear resistance, limiting their use in applications requiring durability, such as automobile interiors, despite offering advantages like flexibility, UV resistance, and flame retardancy over PU and PVC synthetic leathers.
A silicone leather composite material is developed with a textile support layer, a silicone binder layer with 20 to 40 shore A hardness, a silicone skin layer with 50 shore A hardness, and a silicone top coat layer, enhanced by a silicone/polyurethane hybrid plastic-based coating layer, which includes a specific manufacturing process involving multiple curing steps and the use of adhesive promoters and accelerators to improve adhesion and wear resistance.
The composite material achieves improved wear resistance while maintaining flexibility and other advantageous properties, making it suitable for applications previously limited by silicone leather's mechanical weaknesses.
Smart Images

Figure 2025501869000001 
Figure 2025501869000002 
Figure 2025501869000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a silicone leather composite having improved abrasion resistance, a method for producing the silicone leather composite, and uses of the silicone leather composite.
[0002] A variety of synthetic alternatives to natural leather have been developed, mainly using polyurethane (PU) or polyvinyl chloride (PVC) based materials. They are used in a wide variety of applications, including furniture, decoration, handbags, luggage, clothing, footwear, car interiors, car seats, etc. However, to be used as synthetic leather, stringent physical property requirements, e.g., flame retardancy, smoke density, are required to meet increasingly stringent safety regulations, and suitable adhesive strength, heat resistance, stain resistance, solvent resistance, hydrolysis resistance, etc. are required to prevent the coating layer from peeling off during use. PU and / or PVC based materials often fail to meet one or more of the above physical property requirements.
[0003] Silicone-based leather composites provide an additional synthetic alternative to natural leather. Such silicone-based leather composites may have several advantages over the PU and / or PVC-based synthetic leather materials described above. For example, they can be prepared using more environmentally friendly manufacturing methods without the use of plasticizers, toxic heavy metals, or environmentally problematic solvents such as dimethylformamide (DMF), which are often at least partially retained in synthetic PU and / or PVC leather products after manufacture.
[0004] Silicone-based leather composites can be made via several routes, but are generally manufactured using a textile support layer, two or more layers of a hydrosilylation-curable liquid silicone rubber composition, and a release paper. For example, a first liquid silicone rubber (LSR) composition can be coated on the release paper and then cured to form a first layer or skin layer. A second LSR composition, usually having different physical properties from the first layer, is adhered to the cured first layer to form an adhesive layer, and a textile support layer is adhered to the second LSR layer before curing, and then the second LSR composition is cured to form a binder layer located between the skin layer and the textile support layer. If deemed appropriate to form a silicone-based leather composite, one or more additional layers of a hydrosilylation-curable silicone elastomer composition may be applied between the release paper and the textile layer. For example, a third layer may be provided as a protective topcoat on top of the skin layer. The release paper is then removed as needed and when necessary.
[0005] Such silicone-based leather composites can outperform traditional PU and PVC synthetic leathers in terms of physical properties, for example, by their ability to provide better flexibility over a wide temperature range, as well as superior UV, heat, and flame resistance. Topcoats are particularly important because they not only help provide advantageous properties such as stain resistance, but also are gentle on human skin and provide a superior feel to the user.
[0006] However, due to the inherently weak intermolecular interactions between polysiloxane chains, silicone products have the disadvantage of insufficient mechanical strength and therefore poor abrasion resistance.Therefore, the use of silicone leather composites tends to be limited to application scenarios with low abrasion resistance requirements, while PU and PVC synthetic leathers are often used in applications that require good abrasion resistance, such as automotive interiors.
[0007] Therefore, there remains a need to provide a silicone leather composite that has improved abrasion resistance while retaining the physical property advantages compared to PU and PVC based synthetic leathers.
[0008] 1. A silicone leather composite material, comprising: (i) a textile support layer; and (ii) a silicone binder, the silicone binder being a cured product of a two-part hydrosilylation-curable silicone rubber composition designed to adhere to the textile support layer (i) and the skin layer (iii), the silicone binder having a Shore A hardness of 20 to 40 as measured according to ASTM D2240; (iii) a silicone skin layer, the silicone skin layer being a cured product of a two-part hydrosilylation-curable silicone rubber composition containing an adhesion promoter, the silicone skin layer having a Shore A hardness of 50 or greater (≧) as measured according to ASTM D2240; (iv) a silicone topcoat layer that is a cured product of a two-part hydrosilylation-curable silicone topcoat composition that includes an adhesion promoter; a silicone binder (ii) is adhered between the textile substrate (i) and a skin layer (iii), the skin layer (iii) being between the silicone binder layer (ii) and a silicone topcoat layer (iv); A silicone leather composite is provided, characterized in that a silicone / polyurethane hybrid prepolymer-based coating layer (v) having an elastic modulus of 10 MPa or more, determined by calculating the elastic modulus using the initial linear portion of the load-elongation curve according to ASTM D882, is provided in the silicone leather composite between the silicone skin layer (iii) and the silicone topcoat layer (iv).
[0009] Also, there is provided a method for preparing the above silicone leather composite material, comprising the steps of: (a) coating a release paper with a layer of a silicone / polyurethane hybrid prepolymer-based coating composition and curing the composition to provide a silicone / polyurethane hybrid prepolymer-based coating layer (v); (b) applying a layer of a silicone skin composition onto the cured silicone / polyurethane hybrid prepolymer coating layer (v) and curing the composition to provide a silicone skin layer (iii); (c) applying a layer of a silicone binder composition onto the cured silicone skin layer (iii), applying a textile layer (i) onto the silicone binder composition, and curing and / or laminating the composition to form a silicone binder layer (ii) between the textile support layer (i) and the skin layer (iii); (d) removing the release paper from the cured silicone / polyurethane hybrid prepolymer coating layer (v); and (e) applying a layer of a two-part hydrosilylation-curable silicone topcoat composition over the cured silicone / polyurethane hybrid prepolymer coating layer (v) and curing the topcoat composition to form a silicone topcoat layer (iv).
[0010] Textile Support Layer (i) The textile support layer (i) can be made of any suitable textile material, for example, woven, knitted, or nonwoven fabric made of natural fibers, such as cellulose fibers, such as cotton, linen, silk, and wool, and / or synthetic fibers and / or microfibers. Synthetic fibers and / or microfibers can include, but are not limited to, polyester, viscose rayon, polyamide fibers, such as nylon, polyurethane, acrylic, polyolefins, such as polyethylene; and elastic fiber materials, such as spandex, acetate, polylactic acid, glass fiber, and carbon fiber, and can be used as a mixture of any two or more of the above. The textile support layer (i) is designed to increase the mechanical strength of the silicone leather composite.
[0011] Silicone binder layer (ii) The silicone binder layer (ii) is a cured product of a suitable two-part hydrosilylation curable silicone rubber composition designed to adhere to the textile support layer (i) and the skin layer (iii). The selected silicone binder layer (ii) has a relatively low Shore A hardness of 20 to 40 as measured according to ASTM D2240. The silicone binder layer (ii) can be of any desired average dry coat thickness, for example, from 50 μm to 1 mm thick, alternatively from 50 to 750 μm, alternatively from 50 to 500 μm, alternatively from 100 to 500 μm, alternatively from 100 to 300 μm thick. In a preferred embodiment, the silicone binder layer (ii) has a high elongation at break, for example an elongation at break of at least 600% as determined according to ASTM D412, alternatively an elongation at break of at least 750% as determined according to ASTM D412. It may be cured at any suitable temperature, for example, 100-200°C, alternatively 125-180°C, alternatively 130-170°C, alternatively 135-160°C, for a suitable time of 20 minutes or less, alternatively 1-10 minutes, alternatively 1.5 minutes to 5 minutes, alternatively 1.5 minutes to 4 minutes.
[0012] A commercial example of a suitable hydrosilylation curable liquid silicone rubber composition designed to function as a binder layer is Dowsil™ LCF 8400 Binder manufactured by Dow Silicones Corporation. Dowsil™ LCF 8400 Binder is provided to customers in a two-part form to avoid premature curing, and the two parts of Dowsil™ LCF 8400 Binder are mixed together in a 1:1 ratio before use. SILASTIC LCF 8400 Binder is applied to the fabric and cured at a temperature of 100-200°C for 1-10 minutes.
[0013] As previously mentioned, the silicone binder (ii) is designed to be sandwiched between and adhere to both the textile support layer (i) and the skin coating layer (iii).
[0014] Silicone Skin Layer (iii) The silicone skin layer (iii) is a cured product of a two-part hydrosilylation-curable silicone rubber composition containing an adhesion promoter, and the silicone skin layer has a Shore A hardness of 50 or more (≧) when measured according to ASTM D2240. In a preferred embodiment, the silicone skin layer (iii) has an elongation at break of less than 500%, or alternatively 200-400%, determined according to ASTM D412. The silicone skin layer (iii) is designed to form a protective synthetic leather that is typically adhered to the silicone binder (ii), otherwise typically either used alone (i.e., without a topcoat) or sandwiched between the silicone binder (ii) and a suitable topcoat, but as disclosed herein, the silicone skin layer (iii) is sandwiched between the silicone binder (ii) and a silicone / polyurethane hybrid prepolymer-based coating layer (v). Any suitable two-part hydrosilylation-curable silicone rubber composition containing an adhesion promoter can be utilized to form the silicone skin layer (iii) so long as it meets the above requirements. The silicone skin layer (iii) has a Shore A durometer greater than that of the silicone binder (ii) of 50 or more (≧), alternatively from 50 to 90, alternatively from 60 to 90, as measured according to ASTM D2240.
[0015] The silicone skin layer (iii) also includes an adhesion promoter. For example, the adhesion promoter may include one or more of an acryloxysilane, an isocyanatoalkylsilane, a methacrylate, and / or an alkoxysilane having an epoxy group in the molecule.
[0016] The acryloxysilane may include 3-acryloxypropyl-trimethoxysilane, 3-acryloxypropyl-methyldimethoxysilane, 3-acryloxypropyl-dimethyl-methoxysilane, 3-acryloxypropyl-triethoxysilane, or similar acryloxy-substituted alkyl-containing alkoxysilanes.
[0017] The isocyanatoalkylsilane must contain at least one isocyanatoalkyl group per molecule, such as an isocyanatopropyl group, and may be, for example, an (isocyanatoalkyl)trialkoxysilane or an (isocyanatopropyl)dialkoxy(alkyl)silane, in each case where each alkyl group contains 1 to 6 carbons, alternatively 1 to 4 carbons, and each alkoxy group contains 1 to 6 carbons, alternatively 2 to 4 carbons. Specific examples include (3-isocyanatopropyl)trimethoxysilane, (3-isocyanatopropyl)trimethoxysilane, (3-isocyanatopropyl)dimethoxy(methyl)silane, (3-isocyanatopropyl)diethoxy(methyl)silane, (3-isocyanatopropyl)dimethoxy(ethyl)silane, and (3-isocyanatopropyl)diethoxy(ethyl)silane.
[0018] Methacrylates include alkoxysilanes containing methacryl groups, such as methacryloxymethyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyldimethylmethoxysilane, 3-Methacryloxypropyltriethoxysilane, 3-Methacryloxypropylmethyldiethoxysilane, It may include 3-methacryloxyisobutyltrimethoxysilane, or similar methacryloxy-substituted alkoxysilanes.
[0019] Examples of alkoxysilanes having epoxy groups in the molecule that can be used as adhesion promoters may have the formula:
[0020] [ka] In the formula, each R 5 are the same or different and are alkyl groups having 1 to 6 carbon atoms, and each R 6are the same or different and are alkoxy groups having 1 to 6 carbons, where z=0, 1 or 2, or a mixture thereof, in an amount of 1 to 6% by weight of the composition. 5 is an alkyl group having 1 to 3 carbons, or 1 to 2 carbons. 6 is an alkoxy group having 1 to 3 carbons, or 1 to 2 carbons. Preferably, z is 0 or 1, or z is 0. Specific examples include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 4-glycidoxybutyltrimethoxysilane, 5,6-epoxyhexyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
[0021] Alternatively, the adhesion promoter may comprise a mixture and / or reaction product of the following: i) one or more alkoxysilanes having an epoxy group in the molecule as defined above, (ii) an organometallic condensation reaction catalyst comprising an organoaluminum compound or an organozirconium compound; and (iii) A linear organopolysiloxane oligomer containing at least one alkenyl group and at least one hydroxy or alkoxy group per molecule.
[0022] The organometallic condensation reaction catalyst (ii), which comprises an organoaluminum compound or an organozirconium compound, may be selected from organometallic catalysts including zirconates, organoaluminum chelates, and / or zirconium chelates.
[0023] Zirconate catalysts have the general formula Zr[OR 5 ]4[In the formula, each R 5may be the same or different and represent monovalent, primary, secondary or tertiary aliphatic hydrocarbon radicals which may be linear or branched containing 1 to 20 carbon atoms, alternatively 1 to 10 carbon atoms. Optionally, the zirconate may contain partially unsaturated groups. 5 Preferred examples of R include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, tertiary butyl, and branched secondary alkyl groups, such as 2,4-dimethyl-3-pentyl. 5 is the same, preferably, R 5 is an isopropyl group, a branched secondary alkyl group or a tertiary alkyl group, in particular a tertiary butyl group. Specific examples include zirconium tetrapropylate, zirconium tetrabutylate, tetra-isopropyl zirconate, zirconium(IV) tetraacetylacetonate (also called zirconium AcAc4), zirconium(IV) hexafluoroacetylacetonate, zirconium(IV) trifluoroacetylacetonate, tetrakis(ethyltrifluoroacetylacetonate)zirconium, tetrakis(2,2,6,6-tetramethylheptanethionate)zirconium, and the like. Examples of suitable zirconium complexes include zirconium(IV) dibutoxybis(ethylacetonate), zirconium tributoxyacetylacetate, zirconium butoxyacetylacetonate bisethylacetoacetate, zirconium butoxyacetylacetonate bisethylacetoacetate, diisopropoxybis(2,2,6,6-tetramethyl-heptanethionate)zirconium, or similar zirconium complexes with β-diketones (including their alkyl- and fluorine-substituted forms) used as ligands.
[0024] Suitable aluminum-based condensation catalysts include Al(OC3H7)3, Al(OC3H7)2(C3COCH2COC 12 H 25 ), Al(OC3H7)2(OCOCH3), and Al(OC3H7)2(OCOC 12 H 25) may include, but are not limited to, one or more of:
[0025] The organometallic condensation reaction catalyst (ii) may be present in the composition in an amount of from 0.1 to 5% by weight of the composition, alternatively from 0.1 to 3% by weight of the composition, alternatively from 0.1 to 2% by weight of the composition. When the adhesion promoter comprises cumulative amounts of (i), (ii) and (iii), it may comprise from about 0.3 to 6% by weight of the composition, alternatively from 0.3 to 4% by weight of the composition.
[0026] The linear organopolysiloxane oligomer (iii) containing at least one alkenyl group and at least one hydroxy group or alkoxy group per molecule may be, for example, a methylvinylpolysiloxane in which both molecular chain terminals are dimethylhydroxysiloxy units, or a copolymer of methylvinylsiloxane and dimethylsiloxane units in which both molecular chain terminals are dimethylhydroxysiloxy units.
[0027] The organopolysiloxane oligomer (iii) may be a mixture of organopolysiloxane molecules, some of which have silanol end groups at both chain ends, some of which have a silanol group such as a dimethylhydroxysiloxy end unit at only one end, and the other end unit is, for example, a dimethylmethoxysiloxy unit, a trimethylsiloxy unit, or a dimethylvinylsiloxy unit. Preferably, more than 50% by weight of the organopolysiloxane oligomer (iii), more preferably 60 to 100%, contains molecules having silanol end groups at both chain ends.
[0028] The organopolysiloxane oligomer (iii) preferably contains at least 3% by weight, more preferably at least 5% by weight, of vinyl groups and may contain up to 35 or 40% by weight of vinyl groups. Most preferably, the organopolysiloxane oligomer (iii) contains 5 to 30% by weight of vinyl groups. The organopolysiloxane oligomer (iii) preferably has a number average molecular weight of 100 to 10,000 g / mol as measured using gel permeation chromatography using the test GB / T 21863-2008. The organopolysiloxane oligomer (iii) preferably has a viscosity of 0.1 to 300 mPa·s, alternatively 0.1 to 200 mPa·s, alternatively 1 to 100 mPa·s. (Measured using a Brookfield DV 3T Rheometer at 25° C.). The organopolysiloxane oligomer (iii) may be present in the composition in an amount from 0.1 to 5% by weight of the composition, alternatively from 0.1 to 3% by weight of the composition, alternatively from 0.1 to 2% by weight of the composition.
[0029] The silicone skin layer (iii) may be of any suitable average dry coat thickness, for example the binder layer may be of any desired thickness, for example from 50 μm to 1 mm thick, alternatively from 50 to 750 μm, alternatively from 50 to 500 μm, alternatively from 50 to 350 μm, alternatively from 50 to 250 μm thick. It may be cured at any suitable temperature, for example from 100 to 150° C., alternatively from 110 to 135° C., alternatively from 110 to 125° C., for a time from 30 seconds to 5 minutes, alternatively from 30 seconds to 2.5 minutes.
[0030] Apart from the need to incorporate a suitable adhesion promoter as described above, commercial examples of suitable liquid silicone rubber compositions curable to function as skin layer (iii) are Dowsil® LCF 8300 Skin and Dowsil® LCF 8500 Skin, both manufactured by Dow Silicones Corporation, which, given that they are both hydrosilylation-curable liquid silicone rubber compositions, are provided to the user in a two-part format that are mixed together prior to use to avoid premature curing during storage prior to use.
[0031] Both Dowsil® LCF 8300 Skin and Dowsil® LCF 8500 Skin have high Shore A durometer values of 65-70, and Dowsil® LCF 8300 Skin has a relatively low viscosity compared to Dowsil® LCF 8500 Skin. Dowsil® LCF 8500 Skin is a fumed silica reinforced version of the former with high mechanical strength, and therefore has a much higher viscosity. Therefore, if necessary, a mixture of Dowsil® LCF 8300 Skin and Dowsil® LCF 8500 Skin may be used as the silicone skin layer (iii).
[0032] Silicone topcoat layer (iv) Any two-part hydrosilylation curable silicone topcoat composition can be used to prepare the silicone topcoat layer (iv) for the silicone leather composite described herein. The two-part hydrosilylation curable silicone topcoat composition must include an adhesion promoter, such as one of the adhesion promoters considered suitable for the silicone skin layer (iii) above.
[0033] An example of a suitable silicone topcoat (iv) may be the cured product of a composition comprising: Component (iv)(a) one or more organopolysiloxane polymers having at least two unsaturated groups per molecule, the unsaturated groups being selected from alkenyl groups, alkynyl groups, or mixtures thereof, and having a viscosity at 25°C of 100 to 500,000 mPa·s; Component (iv)(b) an optionally hydrophobically treated silica reinforcing filler; component (iv)(c) a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (-Si-H) groups per molecule; Component (iv)(d) a hydrosilylation catalyst; Component (iv)(e) an adhesion promoter as described above with respect to the silicone skin layer (iii), or zirconium acetylacetonate in an amount of 1 to 5 weight percent of the composition; 1,3,5-tris[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in an amount of 1 to 6% by weight of the composition, and / or one or more epoxy silanes of the formula:
[0034] [ka] In the formula, R 5 is an alkyl group having 1 to 6 carbon atoms, and R 6 is an alkoxy group having 1 to 6 carbons, where z=0, 1, or 2, or a mixture thereof; and Component (iv)(f) an eco-solvent; and optionally, Component (iv)(g) Cured silicone powder.
[0035] In such compositions: (iv)(a) Organopolysiloxane polymer Component (iv)(a) of the two-part hydrosilylation-curable silicone topcoat composition is one or more organopolysiloxane polymers having at least two unsaturated groups per molecule, the unsaturated groups being selected from alkenyl groups, alkynyl groups, or mixtures thereof, and having a viscosity at 25°C of 100 to 500,000 mPa·s.
[0036] The organopolysiloxane polymer (iv)(a) has a plurality of groups of formula (I): R a SiO (4-a) / 2 (I) In the formula, each R is independently selected from an aliphatic hydrocarbyl group, an aromatic hydrocarbyl group, or an organyl group (i.e., any organic substituent having one free valence at a carbon atom, regardless of the type of functional group), so long as it contains the requisite number of unsaturated groups. The groups may be in pendant positions (on D or T siloxy groups) or terminal (on M siloxy groups). Saturated aliphatic hydrocarbyls are exemplified by monovalent saturated hydrocarbon groups, i.e., alkyl groups typically containing 1-20 carbon atoms, such as methyl, ethyl, propyl, pentyl, octyl, undecyl, and octadecyl, and cycloalkyl groups, such as cyclohexyl. Unsaturated aliphatic hydrocarbyls are exemplified by alkenyl groups having 2-10 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, isopropenyl, 5-hexenyl, cyclohexenyl, and hexenyl, and alkynyl groups. Aromatic hydrocarbon groups are exemplified by, but are not limited to, phenyl, tolyl, xylyl, benzyl, styryl, and 2-phenylethyl. Organyl groups are exemplified by, but are not limited to, halogenated alkyl groups such as chloromethyl and 3-chloropropyl, nitrogen-containing groups such as amino, amido, imino, and imido groups, oxygen-containing groups such as polyoxyalkylene, carbonyl, alkoxy, and hydroxyl groups. Further organyl groups may include sulfur-, phosphorus-, and / or boron-containing groups. The subscript "a" may be 0, 1, 2, or 3, but is typically predominantly 2 or 3.
[0037] Siloxy groups may be described by an abbreviated nomenclature, i.e., "M," "D," "T," and "Q," where R is an organic group, typically a methyl group. M units are siloxy groups where a=3, i.e., RSiO 1 / 2 and the D unit is a siloxy group where a=2, i.e., RSiO 2 / 2 and the T unit is a siloxy group where a=1, i.e., RSiO 3 / 2 and the Q units are siloxy groups where a=0, i.e., SiO 4 / 2 is equivalent to.
[0038] The molecular structure of the organopolysiloxane polymer (iv)(a) is typically linear, although some branching may be present due to the presence of T groups (described above) within the molecule.
[0039] To achieve useful levels of physical properties in a silicone topcoat layer prepared by curing a two-part hydrosilylation-curable silicone topcoat composition as described above, the viscosity of the organopolysiloxane polymer (iv)(a) should be at least 100 mPa·s at 25° C. The upper viscosity limit of organopolysiloxane polymer (iv)(a) is limited to a maximum viscosity of 500,000 mPa·s at 25° C.
[0040] The amount of unsaturated groups present (wt %) is determined using quantitative infrared analysis in accordance with ASTM E 168. Component (iv)(a) has a viscosity of from 100 mPa·s to 500,000 mPa·s at 25°C, alternatively from 200 mPa·s to 150,000 mPa·s at 25°C, alternatively from 200 mPa·s to 125,000 mPa·s at 25°C, alternatively from 200 mPa·s to 100,000 mPa·s at 25°C, alternatively from 200 mPa·s to 80,000 mPa·s measured at 25°C. The viscosity may be measured using a suitable rotation speed on either a Brookfield® rotational viscometer with spindle LV-4 (designed for viscosities in the range of 1,000 to 2,000,000 mPa.s) or, for viscosities below 1000 mPa·s, a Brookfield® rotational viscometer with spindle LV-1 (designed for viscosities in the range of 15 to 20,000 mPa·s). The organopolysiloxane polymer (iv)(a) may be selected, for example, from polydimethylsiloxanes, alkylmethylpolysiloxanes, alkylarylpolysiloxanes, or copolymers thereof, containing alkenyl and / or alkynyl groups, and may have any suitable end groups, for example, they may be trialkyl-terminated, alkenyldialkyl-terminated, or terminated with any other suitable combination of end groups, provided that each organopolysiloxane polymer (iv)(a) contains at least two unsaturated groups per molecule.
[0041] Thus, the organopolysiloxane polymer (iv)(a) may be, by way of example, a dimethylvinyl-terminated polydimethylsiloxane, a dimethylvinyl-terminated dimethylmethylphenylsiloxane, a trialkyl-terminated dimethylmethylvinylpolysiloxane, or a dialkylvinyl-terminated dimethylmethylvinylpolysiloxane copolymer, although in view of the presence of high levels of alkenyl and / or alkynyl groups such as vinyl groups, a trialkyl-terminated dimethylmethylvinylpolysiloxane or a dialkylvinyl-terminated dimethylmethylvinylpolysiloxane copolymer may be preferred.
[0042] For example, the organopolysiloxane polymer (iv)(a) containing unsaturated groups selected from alkenyl groups and / or alkynyl groups at two termini can be represented by the general formula (II). R'R''R'''SiO-(R''R''SiO) m -SiR'''R''R'' (II)
[0043] In formula (II), each R' may be an alkenyl or alkynyl group, typically containing 2 to 10 carbon atoms. Alkenyl groups include, but are not limited to, vinyl, propenyl, butenyl, pentenyl, hexenyl, alkenylated cyclohexyl groups, heptenyl, octenyl, nonenyl, decenyl, or similar linear and branched alkenyl groups, and alkenylated aromatic ring structures. Alkenyl groups may be selected from, but are not limited to, ethynyl, propynyl, butynyl, pentynyl, hexynyl, alkenylated cyclohexyl groups, heptenyl, octenyl, nonenyl, decynyl, or similar linear and branched alkenyl groups, and alkenylated aromatic ring structures.
[0044] R" does not contain ethylenic unsaturation, and each R" may be the same or different and is independently selected from monovalent saturated hydrocarbon groups, typically containing 1 to 10 carbon atoms, and monovalent aromatic hydrocarbon groups, typically containing 6 to 12 carbon atoms. R" may be unsubstituted or substituted with one or more groups that do not interfere with the cure of the two-part hydrosilylation-curable silicone topcoat compositions described herein, such as halogen atoms. R'" is R' or R", and m is an integer.
[0045] Component (iv)(a) of the two-part hydrosilylation curable silicone topcoat composition can include more than one organopolysiloxane polymer (iv)(a) having a viscosity of 100 to 500,000 mPa·s at 25° C. When a mixture of organopolysiloxane polymers is used in component (iv)(a), at least one, or one, can include at least 5% by weight of the polymer per molecule, or 5 to 15% by weight of the polymer per molecule, or 6 to 15% by weight of the polymer per molecule, or 7 to 15% by weight of the polymer per molecule of unsaturated groups selected from alkenyl groups, alkynyl groups, or mixtures thereof, as can be determined using quantitative infrared analysis according to ASTM E168.
[0046] Component (iv)(a) is typically present in an amount of from 3% or 10% by weight of the two-part hydrosilylation curable silicone topcoat composition to 50% or 45% by weight of the composition, for example, organopolysiloxane polymer (iv)(a) may be present in the range of 10-50%, or 10-45% by weight of the composition.
[0047] (iv)(b) Reinforcing fillers Component (iv)(b) of the two-part hydrosilylation-curable silicone topcoat composition is a reinforcing filler, such as reinforcing silica. Often, silica and other reinforcing fillers (iv)(b) are treated with one or more known hydrophobizing filler treatments to prevent a phenomenon called "creping" or "crepe hardening" during processing of the two-part hydrosilylation-curable silicone topcoat composition.
[0048] Finely divided forms of silica are preferred as reinforcing filler (iv)(b). Precipitated and / or fumed silica, or fumed silica, are particularly preferred due to their relatively high surface area, typically at least 50 m2 / g (BET method according to ISO 9277:2010). Generally, the surface area is between 50 and 450 m2. 2 / g (BET method according to ISO9277:2010), alternatively 50-300m 2 A filler with a surface area of 0.01 μm / g (BET method according to ISO 9277:2010) is used. Both types of silica are commercially available.
[0049] The amount of reinforcing filler (iv)(b) in the two-part hydrosilylation-curable silicone topcoat composition herein is from 5 to 40 wt%, alternatively from 5 to 30 wt%. In some cases, the amount of reinforcing filler can be from 7.5 to 30 wt% based on the weight of the two-part hydrosilylation-curable silicone topcoat composition, alternatively from 10 to 30 wt% of the composition, alternatively from 15 to 30 wt% based on the weight of the composition.
[0050] If the reinforcing filler (iv)(b) is originally hydrophilic (e.g., untreated silica filler), it is typically treated with a treatment agent to make it hydrophobic. The surface treatment makes the filler easily wettable by the organopolysiloxane polymer (iv)(a), so that these surface-modified reinforcing fillers (iv)(b) do not aggregate and can be homogeneously incorporated into the organopolysiloxane polymer (iv)(a). As a result, the mechanical properties of the two-part hydrosilylation curable silicone topcoat composition and the cured material obtained therefrom at room temperature are improved.
[0051] The surface treatment may be carried out prior to introduction into the composition, or may be carried out in situ (i.e., in the presence of at least some of the other components of the compositions herein by blending these components together at room temperature or above until the filler is fully treated). Typically, untreated reinforcing filler (iv)(b) is treated with a treating agent in situ in the presence of organopolysiloxane polymer (iv)(a) and after mixing, a silicone rubber base material is obtained to which other components may be added.
[0052] Typically, the reinforcing filler (ii) can be surface-treated with any applicable low molecular weight organosilicon compound disclosed in the art to prevent creping of the two-part hydrosilylation curable silicone topcoat composition during processing.For example, organosilanes, organopolysiloxanes, or organosilazanes such as hexaalkyldisilazanes, short-chain siloxane diols, or fatty acids, or fatty acid esters such as stearic acid esters, to make the filler hydrophobic, thereby making it easier to handle and obtain a homogeneous mixture with other components. Specific examples include, but are not limited to, silanol-terminated trifluoropropylmethylsiloxane, dimethylsilanol-terminated vinylmethyl (ViMe)siloxane, tetramethyldi(trifluoropropyl)disilazane, tetramethyldivinyldisilazane, silanol-terminated MePh siloxane, liquid hydroxyl-terminated polydiorganosiloxanes containing an average of 2-20 diorganosiloxane repeat groups per molecule, hexaorganodisiloxane, hexaorganodisilazane. A small amount of water may be added with the silica treating agent as a processing aid.
[0053] The filler may be introduced into the two-part hydrosilylation-curable silicone topcoat composition in the form of a masterbatch or base comprising the filler and an organopolysiloxane polymer. The organopolysiloxane polymer used in the masterbatch or base may be of similar structure to component (iv)(a), or alternatively, may be an organopolysiloxane polymer having a viscosity in the same range as component (iv)(a), but with an alkenyl and / or alkynyl content of <5% by weight of the polymer. If necessary, the fumed silica may be rendered hydrophobic in situ by introducing a suitable hydrophobizing agent into the mixture during preparation of the masterbatch.
[0054] The two-part hydrosilylation-curable silicone topcoat compositions described herein are cured using a hydrosilylation cure package that includes an organohydrogenpolysiloxane (iv)(c) having two or more, alternatively three or more, silicon-bonded hydrogen atoms per molecule, and a hydrosilylation catalyst (iv)(d).
[0055] (iv)(c) Organohydrogenpolysiloxane Component (iv)(c) is a crosslinker in the form of a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (-Si-H) groups per molecule.
[0056] Typically, component (iv)(c) contains three or more -Si-H groups, whereby the hydrogen atoms can react with the unsaturated alkenyl or alkynyl groups in component (iv)(a) to form a network therewith, thereby curing the composition. Alternatively, some or all of component (iv)(c) may have two -Si-H groups per molecule, particularly when component (iv)(a) has more than (>) two alkenyl or alkynyl groups per molecule.
[0057] The molecular structure of the polyorganosiloxane (iv)(c) containing at least two or three Si-H groups per molecule is not particularly limited, and may be linear, partially branched linear, cyclic, or silicone resin-based.
[0058] The silicon-bonded organic groups used in component (iv)(c) may be exemplified by alkyl groups such as methyl, ethyl, propyl, butenyl, pentenyl, hexyl, and the like; aryl groups such as phenyl, tolyl, xylyl, and the like; and halogenated alkyl groups such as 3-chloropropyl, 3,3,3-trifluoropropyl, and the like, with methyl and phenyl groups being preferred.
[0059] Examples of polyorganosiloxanes (iv)(c) containing at least two or three silicon-bonded hydrogen groups per molecule include: (a) branched and / or chain extended dimethylhydrogensiloxy terminated polydimethylsiloxanes; (b) dimethylhydrogensiloxy-terminated dimethylsiloxane-methylhydrogensiloxane copolymer; (c)(CH3)2HSiO 1 / 2 Unit: (CH3)3SiO 1 / 2 Units, and SiO 4 / 2 copolymers and / or silicone resins consisting of units; (d)(CH3)2HSiO 1 / 2 Units and SiO 4 / 2 copolymers and / or silicone resins consisting of units; (e)(CH3)2HSiO 1 / 2 Units, SiO 4 / 2 Units and (C6H5)3SiO 1 / 2 copolymers and / or silicone resins consisting of units, and alternatives in which the methyl is replaced by a phenyl group or other alkyl group; (f)(CH3)2HSiO 1 / 2 Groups such as Si-H groups, (CH3)2SiO 2 / 2 Group, and SiO 4 / 2 Silicone resins that contain or consist of groups are included, but are not limited to these.
[0060] The silicone resin may also contain T and / or D groups, or T groups. Other latent crosslinkers (iv)(c) include: (g) 1,1,3,3-tetramethyldisiloxane, (h) 1,3,5,7-tetramethylcyclotetrasiloxane, (i) tris(hydrogendimethylsiloxy)methylsilane, (j) tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, (k) trimethylsiloxy endblocked methylhydrogen polysiloxane; (l) trimethylsiloxy endblocked dimethylsiloxane / methylhydrogensiloxane copolymers; (m) dimethylhydrogensiloxy endblocked dimethylpolysiloxane, (n) dimethylhydrogensiloxy endblocked dimethylsiloxane / methylhydrogensiloxane copolymers; (o) trimethylsiloxy endblocked methylhydrogen siloxane / diphenyl siloxane copolymers; (p) trimethylsiloxy endblocked methylhydrogensiloxane / diphenylsiloxane / -dimethylsiloxane copolymer; (q) trimethylsiloxy endblocked methylhydrogensiloxane / methylphenylsiloxane / -dimethylsiloxane copolymers; (r) dimethylhydrogensiloxy endblocked / dimethylsiloxane / -diphenylsiloxane copolymers, and / or (s) dimethylhydrogensiloxy endblocked methylhydrogensiloxane / dimethylsiloxane / -methylphenylsiloxane copolymers may be mentioned; (t) Others include tetrakis(dimethylsiloxy)silane, hydride terminated, polyphenylmethylsiloxane hydride terminated, polyphenyl-(dimethylhydrosiloxy)siloxane, or phenyltris(dimethylsiloxy)silane, etc. Alternatively, the crosslinker, component (iv)(c), may be a filler, such as silica that has been treated with one of the above.
[0061] In one alternative, the crosslinker (iv)(c) may be a silicone resin comprising a mixture of Q, T, D and / or M groups, such as alternatives (c), (d) and / or (e) above, having a viscosity of 10 to 5000 mPa·s at 25° C., alternatively 10 to 1000 mPa·s at 25° C., alternatively 10 to 500 mPa·s at 25° C.
[0062] Polyorganosiloxane (iv)(c) containing at least two or three -Si-H groups per molecule is typically added in an amount such that the molar ratio of silicon-bonded hydrogen atoms in component (iv)(c) to that of all unsaturated groups in the composition is 0.5:1 to 20:1, alternatively 0.5:1 to 5:1, alternatively 0.6:1 to 3:1. If this ratio is less than 0.5:1, a sufficiently cured composition is not obtained. If this ratio is greater than 20:1, the hardness of the cured composition tends to increase when heated.
[0063] The silicon-bonded hydrogen (Si-H) content of component (iv)(c) is determined using quantitative infrared analysis according to ASTM E168. In the present invention, the ratio of silicon-bonded hydrogen to alkenyl (vinyl) and / or alkynyl is important when relying on the hydrosilylation curing process. Generally, this is determined by calculating the total weight percent of alkenyl groups, e.g., vinyl [V], in the composition and the total weight percent of silicon-bonded hydrogen [H] in the two-part hydrosilylation curable silicone topcoat composition, where the molar ratio of silicon-bonded hydrogen to vinyl is 27 [H] / [V], where the molecular weight of hydrogen is 1 and the molecular weight of vinyl is 27.
[0064] The molecular weight of this component is not particularly limited, but the viscosity is typically 15 to 50,000 mPa·s at 25° C. using a rotational speed of 10 rpm on a Brookfield DV 3T Rheometer or on either a Brookfield® rotational viscometer with spindle LV-4 (designed for viscosities in the range of 1,000 to 2,000,000 mPa·s) or for viscosities below 1000 mPa·s, a Brookfield® rotational viscometer with spindle LV-1 (designed for viscosities in the range of 15 to 20,000 mPa·s).
[0065] Component (iv)(c) of the two-part hydrosilylation-curable silicone topcoat composition is a polyorganosiloxane containing at least two, or alternatively at least three, silicon-bonded hydrogen (-Si-H) groups per molecule which functions as a crosslinker for polymer (iv)(a) by addition reaction of the silicon-bonded hydrogen atoms in component (iv)(c) with the alkenyl and / or alkynyl groups in component (iv)(a) under the catalytic activity of component (iv)(d) described below. Component (iv)(c) contains at least 5,000 parts per million (ppm) silicon-bonded hydrogen (Si-H), alternatively at least 7000 ppm, alternatively from 7000 to 12,000 ppm, alternatively from 8000 to 11,000 ppm, so that the silicon-bonded hydrogen atoms of this component are sufficiently reactive to form a network with the alkenyl and / or alkynyl groups, typically alkenyl groups, especially vinyl groups, of component (iv)(a) to thereby cure the composition. The amount of silicon-bonded hydrogen present is also determined using quantitative infrared analysis according to ASTM E168.
[0066] Component (iv)(c) is typically present in the overall two-part hydrosilylation-curable silicone topcoat composition in an amount of from 5 to 30%, from 5 to 20%, or from 10 to 20% by weight of the composition, the amount present being typically determined by the molar ratio of silicon-bonded hydrogen atoms in component (iv)(c) to the total number of all unsaturated groups, such as alkenyl and alkynyl groups, often vinyl groups, as discussed above.
[0067] (iv)(d) Hydrosilylation catalyst The two-part hydrosilylation-curable silicone topcoat composition is cured via a hydrosilylation (addition) reaction catalyzed by a hydrosilylation (addition cure) catalyst (iv)(d) that is a metal selected from the platinum group metals, i.e., platinum, ruthenium, osmium, rhodium, iridium, and palladium, or a compound of such a metal. Platinum and rhodium compounds are preferred due to the high activity levels of these catalysts in the hydrosilylation reaction.
[0068] The hydrosilylation catalyst (iv)(d) may be a platinum group metal, a platinum group metal deposited on a support, for example, activated carbon, a metal oxide such as aluminum oxide or silicon dioxide, silica gel or powdered charcoal, or a compound or complex of a platinum group metal. Preferably, the platinum group metal is platinum.
[0069] Examples of preferred hydrosilylation catalysts (iv)(d) are platinum-based catalysts such as platinum black, platinum oxide (Adams' catalyst), platinum on various solid supports, chloroplatinic acid such as hexachloroplatinic acid (Pt oxidation state IV) (Speier's catalyst), chloroplatinic acid in a solution of an alcohol such as isooctanol or amyl alcohol (Lamoreaux's catalyst), and complexes of chloroplatinic acid with ethylenically unsaturated compounds such as olefins, and organosiloxanes containing ethylenically unsaturated silicon-bonded hydrocarbon groups, such as tetra-vinyl-tetramethylcyclotetrasiloxane-platinum complex (Ashby's catalyst). Usable soluble platinum compounds include, for example, platinum-olefin complexes of the formula (PtCl2.(olefin)2 and H(PtCl3.olefin), in which in this context it is preferred to use alkenes having 2 to 8 carbon atoms, such as ethylene, propylene, isomers of butene and isomers of octene, or cycloalkanes having 5 to 7 carbon atoms, such as cyclopentene, cyclohexene and cycloheptene. Other soluble platinum catalysts are, for example, platinum-cyclopropane complexes of the formula (PtCl2C3H6)2. , the reaction products of hexachloroplatinic acid with alcohols, ethers, and aldehydes, or mixtures thereof, or the reaction products of hexachloroplatinic acid and / or its conversion products with vinyl-containing siloxanes, such as methylvinylcyclotetrasiloxane, in the presence of sodium bicarbonate in an ethanolic solution. Platinum catalysts with phosphorus, sulfur, and amine ligands can also be used, for example (Ph3P)2PtCl2, and complexes of platinum with vinyl siloxanes, such as sym-divinyltetramethyldisiloxane.
[0070] Therefore, specific examples of suitable platinum-based catalysts of (iv)(d) include: (i) Complexes of chloroplatinic acid and organosiloxanes containing ethylenically unsaturated hydrocarbon groups, as described in U.S. Pat. No. 3,419,593; (ii) Chloroplatinic acid, either in its hexahydrate or anhydrous form; (iii) platinum-containing catalysts obtained by a process comprising reacting chloroplatinic acid with an aliphatically unsaturated organosilicon compound, such as divinyltetramethyldisiloxane; (iv) alkene-platinum-silyl complexes as described in U.S. Pat. No. 6,605,734, such as (COD)Pt(SiMeCl2)2, where "COD" is 1,5-cyclooctadiene, and / or (v) Karstedt's catalyst, which is a platinum divinyltetramethyldisiloxane complex, typically containing about 1% by weight of platinum in a vinylsiloxane polymer. Historically, solvents such as organic solvents such as toluene have been used as alternatives, but the use of vinylsiloxane polymers is a much more preferred choice. These are described in U.S. Pat. Nos. 3,715,334 and 3,814,730. In a preferred embodiment, component (iv)(d) can be selected from platinum coordination compounds. In one embodiment, hexachloroplatinic acid and its conversion products with vinyl-containing siloxanes, Karstedt's catalyst, and Speier's catalyst are preferred.
[0071] The catalytic amount of the hydrosilylation catalyst is generally 0.01 ppm to 10,000 ppm, alternatively 0.01 to 5000 ppm, alternatively 0.01 to 3,000 ppm, alternatively 0.01 to 1,000 ppm, based on the weight of the two-part hydrosilylation curable silicone topcoat composition. In certain embodiments, the catalytic amount of the catalyst may range from 0.01 to 1,000 ppm, alternatively 0.01 to 750 ppm, alternatively 0.01 to 500 ppm, alternatively 0.01 to 100 ppm, based on the weight of the two-part hydrosilylation curable silicone topcoat composition. The ranges may relate to only the metal content in the catalyst or to the entire catalyst (including its ligands), as specified, but typically these ranges relate to only the metal content in the catalyst. The catalyst may be added as a single species or as a mixture of two or more different species. Typically, depending on, for example, the form / concentration in which the catalyst is provided in the polymer or solvent, the amount of component (iv)(d) present will be in the range of 0.001 to 3.0% by weight of the composition, alternatively 0.001 to 2.5% by weight of the composition, or alternatively 0.01 to 2.0% by weight of the two-part hydrosilylation-curable silicone topcoat composition.
[0072] Component (iv)(e) Adhesion promoter Component (iv)(e) is an adhesion promoter used to aid the adhesion of the silicone topcoat (iv) to the silicone / polyurethane hybrid prepolymer coating layer (v). Component (iv)(e) may be any of the adhesion promoters described above. However, one particularly preferred adhesion promoter for use as component (iv)(e) is when the adhesion promoter is a combination of one or more alkoxysilanes having epoxy groups in the molecule and / or 1,3,5-tris[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione as defined above in an amount of 1-6% by weight of the composition, and zirconium acetylacetonate in an amount of 1-5% by weight of the composition.
[0073] In one embodiment, the alkoxysilane having an epoxy group in the molecule is selected from 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and / or 3-glycidoxypropylmethyldimethoxysilane.
[0074] Component (iv)(f) Eco-solvent Component (iv)(f) of the two-part hydrosilylation curable silicone topcoat composition is an eco-solvent. Any suitable eco-solvent may be utilized, examples of which include isopentadecane, isohexadecane, isoheptadecane, isooctadecane, isononadecane, and mixtures thereof, or trimethyl-terminated polydimethylsiloxanes having a viscosity of 5 mPa·s or more (≧) at 25° C. to 100 mPa·s or less (≦) at 25° C. It has been noted that the use of trimethyl-terminated polydimethylsiloxanes having a viscosity of <5 mPa·s at 25° C. actually appears to result in leather materials with white stretch marks. In one embodiment, the eco-solvent comprises or consists of isohexadecane. The eco-solvent is present in the composition as a means of diluting the composition, and is present in the composition in an amount of 30-70% by weight of the two-part hydrosilylation curable silicone topcoat composition. It may be present in either or both Part A and Part B, as desired or required.
[0075] Component (iv)(g) Optional cured silicone elastomer powder Any suitable cured silicone elastomer powder may be utilized in the two-part hydrosilylation curable silicone topcoat composition, as desired. In one alternative, the cured silicone elastomer powder (iv)(g) has an average particle size of 0.01 to 100 μm, alternatively 0.01 to 50 μm, alternatively 0.01 to 25 μm, as measured, for example, using Dow Silicone Corporation Corporate Test Method CTM 1138, which is publicly available upon request. They may contain chemical functional groups, such as epoxy groups, (meth)acryloxy groups, or may be coated, for example, with a silica-treated coating.
[0076] The cured silicone elastomer powder is made from a suitable curable silicone composition. The curable silicone composition may include, for example, an addition (hydrosilylation) reaction curing silicone composition, a condensation reaction curing silicone composition, an organic peroxide curing silicone composition, and an ultraviolet light curing silicone composition. The addition reaction curing and condensation reaction curing silicone compositions are preferred due to their ease of handling.
[0077] Silicone elastomer powders are generally prepared by first dispersing the curable silicone composition in water or an aqueous surfactant solution, and then subjecting the dispersion to the action of a mixer such as a homogenizer, a colloid mill, or an ultrasonic vibrator to create a homogeneous aqueous emulsion of the curable silicone composition. In order to obtain a very stable emulsion in which the curable silicone composition has a small average particle diameter, the aqueous curable silicone emulsion is preferably prepared using a surfactant. An aqueous dispersion of cured silicone powder is then produced by curing the curable silicone present in the aqueous emulsion. This curing can be affected by leaving the aqueous emulsion at room temperature or by heating the aqueous emulsion. When heating the aqueous curable silicone emulsion, the preferred heating temperature should not exceed 100°C, and a particularly preferred temperature is in the range of 40°C to 95°C. The technique for heating the water-based curable silicone emulsion is by directly heating the water-based emulsion or by adding the water-based emulsion to hot water. Commercial examples that can be used as component (iv)(g) include, for example, Dowsil® 23N Additive, Dowsil® 603T additive, and Dowsil® 9701 Cosmetic Powder manufactured by Dow Silicones Corporation.
[0078] The cured silicone rubber powder is present in the two-part hydrosilylation curable silicone topcoat composition, i.e., when Part A and Part B are mixed together, in an amount of 2.5 to 20% by weight of the composition, alternatively 2.5 to 15% by weight of the composition, alternatively 2.5 to 10% by weight of the composition.
[0079] Optional Additives The two-part hydrosilylation-curable silicone topcoat composition may contain one or more additives. Examples of these optional additives include cure inhibitors, inorganic non-reinforcing fillers, conductive additives, pot life extenders, lubricants, flame retardants, pigments, colorants, chain extenders, heat stabilizers, compression set improving additives, anti-squeak agents, antioxidants, antistatic agents, antifouling agents, and light stabilizers, antifreeze agents, and / or biocides, and mixtures thereof.
[0080] Inhibitor Because a hydrosilylation cure system is utilized, in order to obtain a longer working or pot life of the two-part hydrosilylation-curable silicone topcoat composition, a suitable inhibitor may optionally be incorporated into the composition to retard or inhibit the activity of the catalyst.
[0081] Inhibitors for platinum metal catalysts, and generally platinum group metal catalysts, are well known in the art. Hydrosilylation or addition reaction inhibitors include hydrazines, triazoles, phosphines, mercaptans, organic nitrogen compounds, acetylenic alcohols, silylated acetylenic alcohols such as methyl(tris(1,1-dimethyl-2-propynyloxy))silane, maleates, fumarates, ethylenically or aromatically unsaturated amides, ethylenically unsaturated isocyanates, olefinic siloxanes, unsaturated hydrocarbon monoesters and diesters, conjugated ene-ynes, hydroperoxides, nitriles, and diaziridines. Alkenyl-substituted siloxanes, such as those described in U.S. Pat. No. 3,989,667, may also be used, of which cyclic methylvinylsiloxanes are preferred.
[0082] Another known class of platinum catalyst inhibitors includes the acetylenic compounds disclosed in U.S. Patent No. 3,445,420. Acetylenic alcohols such as 2-methyl-3-butyn-2-ol constitute a preferred class of inhibitors that suppress the activity of platinum-containing catalysts at 25° C. Hydrosilylation-curable silicone elastomer compositions containing these inhibitors typically must be heated to temperatures of 70° C. or above in order to cure at a practical rate.
[0083] Examples of acetylenic alcohols and their derivatives include 1-ethynyl-1-cyclohexanol (ETCH), 2-methyl-3-butyn-2-ol, 3-butyn-1-ol, 3-butyn-2-ol, propargyl alcohol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclopentanol, 1-phenyl-2-propynol, 3-methyl-1-penten-4-yn-3-ol, and mixtures thereof.
[0084] In some cases, inhibitor concentrations as low as 1 mole of inhibitor per mole of metal of catalyst (iv)(d), when present, provide satisfactory storage stability and cure speed. In other cases, inhibitor concentrations of up to 500 moles of inhibitor per mole of metal of catalyst (iv)(d) are required. The optimum concentration for a given inhibitor in a given composition is easily determined by routine experimentation. When present in the composition, the inhibitor is typically present in an amount of 0.0125-10% by weight of the two-part hydrosilylation-curable silicone topcoat composition, depending on the concentration and form in which the selected inhibitor is provided / commercially available. Mixtures of the above may also be used.
[0085] Where optional additives may be used for more than one reason, for example, as a non-reinforcing silica filler and a flame retardant, when present, they can function in both roles. When or if present, the aforementioned additional components are present in an amount, cumulatively, of 0.1 to 30% by weight, alternatively 0.1 to 20% by weight, of the two-part hydrosilylation-curable silicone topcoat composition.
[0086] To prevent premature curing during storage, the two-part hydrosilylation-curable silicone topcoat composition will be stored prior to use in two parts, Part A and Part B. Typically, Part A contains the organopolysiloxane polymer (iv)(a) and a portion of the reinforcing filler (iv)(b), as well as the hydrosilylation catalyst (iv)(d), and Part B contains the remaining organopolysiloxane polymer (iv)(a) and reinforcing filler (iv)(b), along with the organohydrogenpolysiloxane crosslinker (iv)(c), and usually an inhibitor, if present, although this can vary depending on the choice of inhibitor used. The two-part composition may be designed to be mixed together in any suitable ratio depending on the amount of organopolysiloxane polymer (iv)(a) and reinforcing filler (iv)(b) of Part B, and thus may be mixed in a weight ratio of Part A:Part B of from 15:1 to 1:2, but preferably is mixed in a weight ratio of Part A:Part B of from 2:1 to 1:2, alternatively from 1.5:1 to 1:1.5, alternatively 1:1.
[0087] After mixing, the two-part hydrosilylation-curable silicone topcoat composition is cured for 2 to 8 minutes at a temperature of 120° C. to 175° C., alternatively 130° C. to 160° C. The average dry coat thickness of the two-part hydrosilylation-curable silicone topcoat is 5 to 20 μm.
[0088] Silicone / polyurethane hybrid prepolymer coating layer (v) The silicone leather composite described herein contains a silicone / polyurethane hybrid prepolymer coating layer (v) having a modulus of elasticity determined according to ASTM D882 of 10 MPa or more, or 20 MPa or more, or 30 MPa or more, determined according to ASTM D882, in each case using the first linear part of the load-elongation curve to calculate the modulus of elasticity. The silicone / polyurethane hybrid prepolymer coating layer (v) is provided in the silicone leather composite between the silicone skin layer (iii) and the silicone top coat (iv). It has been found that the addition of such a layer provides the silicone leather composite with a significant improvement in abrasion resistance.
[0089] For the avoidance of doubt, it should be understood that, like polyurethane prepolymers, silicone / polyurethane hybrid prepolymers are those in which all hydroxyl end groups have been reacted with isocyanate groups, leaving terminal isocyanate functional groups in place of hydroxyls.
[0090] The silicone / polyurethane hybrid prepolymer-based coating layer (v) is provided by curing a suitable silicone / polyurethane hybrid prepolymer-based coating composition. The composition is prepared in a suitable solvent, and the solvent evaporates during the heat curing process. The following discussion of the potential components of a suitable silicone / polyurethane hybrid prepolymer-based coating composition, when discussing the weight percent of the composition, refers to the weight percent of the solute components, and ignores the presence of a solvent if the solvent does not form part of the resulting silicone / polyurethane hybrid prepolymer-based coating layer (v) of the silicone leather composite material described herein. The silicone / polyurethane hybrid prepolymer-based coating composition can be prepared in any desired manner, provided that the resulting silicone / polyurethane hybrid prepolymer-based coating layer (v) meets the specific requirements required herein for the silicone rubber composite material.
[0091] Silicone / polyurethane hybrid prepolymers suitable for silicone / polyurethane hybrid prepolymer-based coating compositions can be prepared, for example, using two or three components: Component 1 is a carbinol-terminated polydialkylsiloxane polymer having a hydroxyl number of greater than or equal to 40 mg KOH / g as measured in accordance with ASTM-D4274-11.
[0092] Typically, the carbinol-terminated polydialkylsiloxane polymer is a carbinol-terminated polydimethylsiloxane polymer. For the avoidance of doubt, a terminal carbinol (C-OH) group is a C-OH bonded to a terminal silicon via a suitable non-hydrolyzable organic bond, such as: -Z 5 z’ -D d -OH In the formula, Z 5 is a divalent alkylene group containing 1 to 6 carbons, alternatively 2 to 6 carbons, alternatively 2 to 4 carbons, z' is 0 or 1, and D is an average formula (-OC n’ H 2n’ ), where n' is an integer from 2 to 6, and d is an integer from 1 to 6, alternatively from 2 to 4. Suitable commercially available carbinol-terminated polydimethylsiloxanes include, for example, DOWSIL™ BY16-201 available from Dow Silicones corporation, and KF 6000 and KF-6001 available from Shin-Etsu Chemical Co. Ltd. Component 2 is a polyisocyanate, for example, an aromatic polyisocyanate such as polymethylene polyphenyl polyisocyanate, diphenylmethane diisocyanate, polymeric diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, xylylene diisocyanate, phenylene diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; an aliphatic or cycloaliphatic polyisocyanate such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate, and tetramethylxylylene diisocyanate, or a mixture of two or more thereof may be used. The aliphatic or cycloaliphatic polyisocyanate is preferably, for example, IPDI. Also, optionally, Component 3 is a short chain organic diol having 2 to 6 carbons per molecule, such as ethylene glycol, 1,3-propanediol, and / or 1,4-butanediol. The hydroxyl content of component 3, if present, can also be measured according to ASTM-D4274-11.
[0093] In one embodiment, the ratio of NCO groups to OH groups in components 1, 2, and, if present, component 3, is at least 0.95:1, alternatively from 0.95 to 1.05, and the NCO content is Measured according to ASTM D5155, the NCO / OH ratio is calculated from the NCO content of component 2 and the cumulative hydroxyl number of components 1 and 3 (if present).
[0094] The solute components (i.e., components excluding the solvent) of the silicone / polyurethane hybrid prepolymer based coating composition that is cured to provide the silicone / polyurethane hybrid prepolymer based coating layer (v) can include, for example, the following: (v)(a) a prepolymer reaction product obtained from the reaction of components 1, 2, and optionally 3, preferably components 1, 2, and 3; (v)(b) an optional cured silicone elastomer powder, which may be selected from the same particles as described with respect to component (iv)(g) above; (v)(c) any silicon-free organic particles and / or particulates selected from at least one of polymethyl methacrylate (PMMA), ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), or polyurethane polymers; alternatively, the silicon-free organic particles and / or particulates (v)(c) are selected from PMMA and / or polyurethane particles and / or particulates. For the avoidance of doubt, silicon-free organic particles or particulates are silicon-free and tolerate only trace amounts of contamination, i.e., silicon-free organic particulates are substantially free of silicon atoms or silicon-containing compounds. In one alternative, the silicon-free organic particles or particulates have a number average particle size of 0.5 to 500 μm as determined using a field emission scanning electron microscope, such as a FEI Nova NanoSEM™ 630 scanning electron microscope from Thermo Fisher Scientific. For example, this can be accomplished by taking a field emission scanning electron micrograph of the particles, then randomly selecting 10 particles from the photograph and measuring the diameter of each particle in the image. The average diameter is then calculated for the selected particles. The silicon-free inorganic particles or microparticles are preferably thermally stable up to a temperature of at least 180°C. They are required to be thermally stable throughout the curing process, which is typically held at a temperature of 80°C to 180°C. By "thermally stable" it is meant that the silicon-free inorganic particles or microparticles do not thermally decompose at temperatures below 180°C. This is determined by placing a sample of the silicon-free inorganic particles or microparticles in a suitable container and then placing the container in a preheated oven at a temperature of 180°C and atmospheric pressure for 30 minutes. After placing in the oven for 30 minutes, the samples are visually evaluated to determine whether the particles or particulates appear to be in their original form, in which case they are deemed thermally stable (pass) up to a temperature of 180°C, or whether they have been visually decomposed in some manner that is visually evident, for example by agglomeration, liquefaction, carbonization, and / or decomposition. (v)(d) is a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (—Si—H) groups per molecule, which may be selected from any one of the crosslinkers defined in (iv)(c) above, typically present in an amount of 1% to 10% by weight of the composition used to prepare the silicone / polyurethane hybrid prepolymer-based coating layer (v) described above, but is preferably a resinous crosslinker; (v)(e) an optional curing catalyst for curing the silicone / polyurethane hybrid prepolymer based coating composition; (v)(f) a polyether polyol having at least two hydroxyl groups per molecule and a hydroxyl number greater than (>) 100 mg KOH / g according to ASTM-D4274-11; and (v)(g) a platinum group metal based catalyst which may be the same as any of the hydrosilylation catalysts (iv)(d) above, where the platinum group metal is platinum, ruthenium, osmium, rhodium, iridium, and palladium, or a compound of such metals. Typically, the platinum group metal based catalyst (v)(g) is a platinum or ruthenium based catalyst, or a platinum based catalyst as described with respect to (iv)(d), with Karstedt's catalyst being preferred.
[0095] Any suitable solvent can be utilized to aid in the preparation of the silicone / polyurethane hybrid prepolymer-based coating composition. As previously mentioned, such solvent is selected to evaporate during the curing process.
[0096] In a preferred embodiment, the total amount of particles in the silicone / polyurethane hybrid prepolymer based coating composition used to prepare the silicone / polyurethane hybrid prepolymer based coating layer (v) is their weight percent, i.e. (v)(b)+(v)(c), between 10% and 40% by weight of the composition.
[0097] In the silicone / polyurethane hybrid prepolymer based coating composition, the polyorganosiloxane (v)(d) containing at least two, alternatively at least three, silicon-bonded hydrogen (—Si—H) groups per molecule may be, for example, a Si-H dimethyl endgroup MQ resin, such as a Si-H dimethyl endgroup polysiloxane having a viscosity of 25 mPa·s at 25° C. and a silicon-bonded hydrogen content of about 9,000 ppm.
[0098] The optional polyurethane cure catalyst (v)(e) of the silicone / polyurethane hybrid prepolymer based coating composition may comprise any suitable known polyurethane catalyst, such as tin, bismuth, zinc, mercury catalysts, i.e. Sn, Bi, Zn, Hg catalysts, preferably Bi / Zn catalysts. Examples include carboxylates of tin, bismuth, zinc, and / or mercury. Suitable tin catalysts include, for example, tin triflate, organotin metal catalysts such as triethyltin tartrate, tin octoate, tin oleate, tin naphthenate, butyltin tri-2-ethylhexanoate, tin butyrate, carbomethoxyphenyltin trisperate, isobutyltin triceroate, and diorganotin salts, in particular diorganotin dicarboxylate compounds such as dibutyltin dilaurate (DBTDL), dioctyltin dilaurate (DOTDL), dimethyltin dibutyrate, dibutyltin dimethoxide, dibutyltin diacetate (DBTDA), dibutyltin bis(2,4-pentanedionate), dibutyltin dibenzoate, stannous octoate, dimethyltin dineodecanoate, and the like. Examples of tin catalysts (v)(e) include dibutyltin dilaurate-based catalysts available from Evonik under the trade name Dabco® T-12.
[0099] Alternatively, the optional polyurethane curing catalyst (v)(e) in the silicone / polyurethane hybrid prepolymer based coating composition, when present, may be a suitable Bi / Zn catalyst, i.e., an organobismuth / zinc complex catalyst designed to catalyze the reaction of -NCOs groups with -OH groups for polyurethane products, such as that commercially available under the trade name BX-EM 23 from Guangzhou Yourun Synthetic Material Co., Ltd (Guang Dong, China).
[0100] When present, the optional polyurethane cure catalyst (v)(e) may be present in an amount of 0.01 to 3 weight percent of the composition, alternatively 0.03 to 1.5 weight percent of the silicone / polyurethane hybrid prepolymer based coating composition, alternatively 0.03 to 0.75 weight percent of the composition.
[0101] The polyether polyol (v)(f) has at least two hydroxyl groups per molecule, alternatively at least three hydroxyl groups per molecule, and has a hydroxyl number of >100 mg KOH / g according to ASTM-D4274-11. The polyether polyol (v)(f) has an average formula of (-C n H 2n -O-) ywhere n is an integer from 2 to 6 and y is an integer, or an integer of at least 2, and need not be the same throughout the polyoxyalkylene but may vary from unit to unit, such as ethylene oxide units (-[CH2-CH2-O]-), trimethylene oxide units (-[CH2-CH2-CH2-O]-), tetramethylene oxide units (-[CH2-CH2-CH2-CH2-O]-), oxypropylene units (-[CH(CH3)-CH2-O]-), and / or oxybutylene units (-[CH(CH2CH3)-CH2-O]-). The polyether polyol (v)(f) may be, for example, a commercially available polyether triol having a hydroxyl value of 647-676 mg KOH / g sold under the trade name VORANOL CP 260 Polyol by Dow Chemical Co., or a commercially available polyether triol having a hydroxyl value of 370-396 mg KOH / g sold under the trade name VORANOL CP 450 Polyol by Dow Chemical Co., and polyether polyol HF-302 commercially available from Zhejiang Hengfeng New Material Co., Ltd. The content of the polyether polyol (v)(f) is 10% by weight to 30% by weight in the silicone / polyurethane hybrid prepolymer coating composition used to prepare the silicone / polyurethane hybrid prepolymer coating layer (v) described above.
[0102] The silicone / polyurethane hybrid prepolymer coating composition used to prepare the silicone / polyurethane hybrid prepolymer coating layer (v) is stored in two parts, a first part and a second part. The polyether polyol (v)(f) and the platinum group metal catalyst (v)(g) are separated from the remaining components during storage (in the second part). The optional tin or Bi / Zn catalyst, if present, may be present in the first part or the second part, and all remaining components are kept in the first part until mixed together.
[0103] All weight percent values given above for the silicone / polyurethane hybrid prepolymer based coating composition used to prepare the aforementioned silicone / polyurethane hybrid prepolymer based coating layer (v) are exclusive of the solvent content.
[0104] The solvent will vary depending on the components, but may include any suitable solvent, such as, for example, ethylene glycol dibutyl ether, and / or one or more esters of glycol ethers, such as (but not limited to) those selected from ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, propylene glycol diacetate, and dipropylene glycol monoethyl ether acetate.
[0105] The composition may be cured at a temperature of 100° C. to 200° C. for 2 to 10 minutes.
[0106] The average dry coat thickness of the silicone / polyurethane hybrid prepolymer-based coating layer (v) is 10 μm to 50 μm, which was determined by measuring the length and width of a release paper sample, coating the release paper with a silicone / polyurethane hybrid prepolymer-based coating composition, curing it, weighing the resulting release paper coated with the silicone / polyurethane hybrid prepolymer-based coating layer (v), and calculating the average thickness based on the following formula: Average dry coat thickness of layer (v) = weight of layer (v) / (density * width * length)
[0107] Where indicated, the average dry coat thickness of each layer was determined by determining the weight of each layer and using the formula above, as was the thickness of layer (v). In each case, the density was determined according to ASTM D792. As previously mentioned, there is also provided a method for preparing the silicone leather composite described herein. The process comprises: (a) coating a release paper with a layer of a silicone / polyurethane hybrid prepolymer-based coating composition and curing the composition to provide a silicone / polyurethane hybrid prepolymer-based coating layer (v); (b) applying a layer of a silicone skin composition onto the cured silicone / polyurethane hybrid prepolymer coating layer (v) and curing the composition to provide a silicone skin layer (iii); (c) applying a layer of a silicone binder composition onto the cured silicone skin layer (iii), applying a textile layer (i) onto the silicone binder composition, and curing and / or laminating the composition to form a silicone binder layer (ii) between the textile support layer (i) and the skin layer (iii); (d) removing the release paper from the cured silicone / polyurethane hybrid prepolymer coating layer (v); and (e) applying a layer of a two-part hydrosilylation curable silicone topcoat composition over the cured silicone / polyurethane hybrid prepolymer coating layer (v) and curing the topcoat composition to form a silicone topcoat layer (iv).
[0108] It was found that problems were encountered when applying a two-part hydrosilylation curable silicone topcoat composition onto a release paper as the first step in the process, followed by application of the silicone / polyurethane hybrid prepolymer based coating composition (v), and surprisingly, the problems were avoided by adding a topcoat onto the cured silicone / polyurethane hybrid prepolymer based coating layer (v) as the last step, thus developing the above process.
[0109] In one embodiment of the manufacturing process, the process comprises: (a) coating a release paper with a layer of a silicone / polyurethane hybrid prepolymer-based coating composition and curing at a temperature between 120° C. and 180° C. for 2 to 10 minutes to form a silicone / polyurethane hybrid prepolymer-based coating layer (v) to obtain an average dry coat thickness of 10 μm to 50 μm using the method described above; (b) applying a layer of a silicone skin composition onto the cured silicone / polyurethane hybrid prepolymer based coating layer (v) and curing at any suitable temperature, for example 100-150° C., to produce a silicone skin layer (iii) having an average dry coat thickness of 50 μm to 1 mm, alternatively 50 to 750 μm, alternatively 50 to 500 μm, alternatively 50 to 350 μm, alternatively 50 to 250 μm, alternatively 70 μm to 200 μm using the methods described above; (c) applying a layer of a silicone binder composition onto the cured silicone skin layer (iii), applying a textile layer (i) onto the silicone binder, and curing and / or laminating the silicone binder (ii) between the textile support layer (i) and the skin layer (iii) at a temperature of 130°C to 180°C for 2 to 8 minutes, the thickness of the resulting layer being determined by the thickness requirements of the silicone leather composite and the thicknesses of the other layers; (d) removing the release paper from the cured silicone / polyurethane hybrid prepolymer coating layer (v); and (e) applying a layer of a two-part hydrosilylation curable silicone topcoat composition onto the cured silicone / polyurethane hybrid prepolymer coating layer (v) and curing the topcoat at 130°C-160°C for 2-8 minutes to form a silicone topcoat (v) having an average dry coat thickness of 5-20 μm using the method described above, thereby completing the silicone leather composite.
[0110] The individual parts of each of the two-part hydrosilylation compositions described above can be prepared in any suitable manner. Any mixing technique and equipment described in the prior art can be used for this purpose. The specific equipment used will be determined by the viscosity of the components and the respective final curable compositions. Suitable mixers include, but are not limited to, paddle-type mixers, such as planetary mixers, and kneader-type mixers. It may be desirable to cool the components during mixing to avoid premature curing of the composition. Thus, as a first step in the process, part A and part B of each two-part composition are mixed together, and the composition may be degassed if desired, for example, for the skin layer and binder layer in the case of the two-part hydrosilylation composition.
[0111] The order of mixing the components in the hydrosilylation-curable silicone elastomer composition of the two-part hydrosilylation-curable silicone topcoat composition is not important. The appropriate Part A and Part B are prepared, and then immediately prior to use, Part A and Part B are mixed together in a predetermined weight ratio of 15:1 to 1:2, for example, a ratio of 1:1.
[0112] After preparation and / or mixing, each composition utilized to provide a respective layer in the silicone leather composite may be applied according to the process described above using any suitable application method, such as spraying, rolling, brushing, spin coating, dip coating, solvent casting, slot die coating, spray coating, knife coating, or gravure coating.
[0113] Any suitable release paper can be used, such as super matte release paper ARX175DM manufactured by Japan Asahi Co., Ltd., release papers DE-7, DE-90, DE-43C, DE-73J manufactured by Dai Nippon Printing Co., Ltd. (Japan), or semi-matte release paper DE-73M also manufactured by Dai Nippon Printing Co., Ltd. (Japan).
[0114] Each curing step may be carried out in a suitable oven, for example by curing and drying in a hot air oven, or in a conveyor oven for a continuous process.
[0115] If desired, the final silicone leather composite may be post-cured at a temperature of about 75° C. to 180° C., generally, but not necessarily, towards the lower end of the range if desired, e.g., 75 to 120° C., for 2 to 48 hours, alternatively 6 to 36 hours, alternatively 10 to 24 hours.
[0116] Silicone leather composites can be designed to have a wide variety of properties considering the content of different layers, for example, excellent flame retardancy, smoke density, heat resistance, stain resistance, solvent resistance, hydrolysis resistance, etc. depending on the requirements of the end use of the leather. Meanwhile, the provision of the silicone / polyurethane hybrid prepolymer-based coating layer (v) resulted in significantly improved abrasion resistance.
[0117] Contemplated end uses include, but are not limited to, furniture, décor, handbags, binders, luggage, clothing, phone covers, covers for electronic items, book covers, footwear, automotive interiors, automotive seats, medical beds / seats, wearable devices, and the like. EXAMPLES
[0118] In the following examples and comparative examples, several silicone leather composites were prepared and tested to demonstrate the advantage of incorporating a silicone / polyurethane hybrid prepolymer-based coating layer (v) as a means of improving abrasion resistance. All viscosities are measured at 25°C. Viscosities were measured using a Brookfield DV 3T Rheometer or either a Brookfield® rotational viscometer with spindle LV-4 (designed for viscosities in the range of 1,000 to 2,000,000 mPa·s) or for viscosities below 1000 mPa·s, a Brookfield® rotational viscometer with spindle LV-1 (designed for viscosities in the range of 15 to 20,000 mPa·s) using a rotation speed of 10 rpm.
[0119] The amount of unsaturated groups and / or silicon-bonded hydrogen present (wt %) was determined using quantitative infrared analysis according to ASTM E168.
[0120] Two prepolymers were prepared by reacting carbinol-terminated polydimethylsiloxane with 1,4-butanediol (chain extender) and isophorone diisocyanate (IPDI).
[0121] Carbinol-terminated PDMS1 was a monoethylene glycol-terminated polydimethylsiloxane having a viscosity of about 48 mPa·s at 25° C. and about 60 mg KOH / g as measured according to ASTM-D4274-11. Carbinol-terminated PDMS1 is commercially available from Dow Silicones Corporation under the trade name DOWSIL™ BY16-201.
[0122] The carbinol-terminated PDMS2 was a polydimethylsiloxane doubly terminated with -C3H6-0-C2H4-OH linear carbinol groups bonded to the terminal silicon, with a viscosity of about 45 mPa·s at 25° C. and about 62 mg KOH / g (supplier information). Carbinol-terminated PDMS2 is commercially available from Shin-Etsu Chemical Co. Ltd under the trade name KF-6001.
[0123] Isophorone diisocyanate (IPDI) has the following structure:
[0124] [ka]
[0125] The amount of each starting component for producing the silicone / polyurethane hybrid prepolymer of the example is shown in Table 1a. The reaction was carried out for 3 hours at a temperature of about 70°C in the presence of dipropylene glycol methyl ether acetate (DPMA) as a solvent. The resulting prepolymer product is not extracted from the solvent upon completion, but is mixed in solution with the other components of the composition. Meanwhile, the solvent evaporates during the curing process.
[0126] [Table 1]
[0127] Four silicone / polyurethane hybrid prepolymer-based coating compositions (SPHPT1-4) were then prepared utilizing one or other of the prepolymers listed above. First, the compositions were prepared in two parts, each containing some solute components in a solvent. The solute components other than the prepolymers listed above are as follows: The silicone elastomer powder used was commercially available from Dow Silicones Corporation under the trade name Dowsil® 23N Additive, and had an average particle size of 2 μm and a particle size distribution of 1-10 μm, both as determined by Dow Silicones Corporation corporate test method CTM1138, which is publicly available upon request. The polyurethane microparticles used in the composition have an average particle size of 1 to 10 μm (supplier information) and are commercially available from Dainichiseika Color & Chemicals Mfg. Co. Ltd under the trade name RHU-5070D Polyurethane Microparticles; Polymethylmethacrylate (PMMA) particles are crosslinked acrylic mid-dispersion particles with a narrow particle size distribution, averaging about 5 μm (supplier information), commercially available under the trade name Chemisnow® MZ-5HN by Soken Chemical & Engineering; The tin catalyst used was a dibutyltin dilaurate catalyst available from Evonik under the trade name Dabco® T-12; The Bi / Zn catalyst is an organobismuth / zinc complex catalyst designed to catalyze the reaction of NCOs groups with -OH groups for polyurethane products, and is commercially available from Guangzhou Yourun Synthetic Material Co., Ltd (Guang Dong, China) under the trade name BX-EM 23; The polyether triol used in the examples had an average molecular weight of 260 and was commercially available from Dow Chemical under the trade name VORANOL™ CP 260 Polyol; The resinous Si-H crosslinker is a Si-H dimethyl terminated resinous Si-H polysiloxane having a viscosity of 25 mPa·s at 25°C and a silicon-bonded hydrogen content of approximately 9,000 ppm. The solute components of each Part A composition are shown in Table 2a and the solute components of the Part B composition are shown in Table 2b. The solute components of each Part A and Part B composition were dissolved in an appropriate solvent and the weight percentages of the solute components of Part A and the solute components of Part B cumulatively added up to 100% by weight, excluding any solvent present, which evaporated during the preparation, processing, and especially the curing process.
[0128] [Table 2]
[0129] [Table 3]
[0130] The elastic modulus (MPa) of SPHPT1-4 was determined by preparing the Part A and Part B compositions in an appropriate solvent. The two parts were mixed together and then coated onto an aluminum plate and placed in an oven at a temperature of 130°C-150°C for 30 minutes to cure the coating and evaporate the solvent, then the resulting cured films were removed from the plate and tested for their elastic modulus according to ASTM D882, and the initial linear portion of the load-elongation curve was used to calculate the elastic modulus. The elastic modulus results were 117 MPa for SPHPT1, 59 MPa for SPHPT2, 116 MPa for SPHPT3, and 39 MPa for SPHPT4.
[0131] A two-part silicone leather topcoat of the type disclosed in applicant's unpublished PCT application PCT / CN21 / 080128 at the time of filing this application was prepared according to the following composition, and the same topcoat was utilized in all examples (where included in the silicone leather composite). The formulations used in the examples are shown below in Tables 3a and 3b.
[0132] [Table 4]
[0133] [Table 5]
[0134] The components of Tables 3a and 3b are as defined above or below. The vinyl-terminated siloxane polymer is a dimethylvinyl-terminated polydimethylsiloxane having a vinyl content of about 0.08% by weight, with a viscosity of 65,000 mPa·s at 25° C. The high vinyl siloxane copolymer is a dimethylvinyl terminated dimethylmethylvinyl polysiloxane copolymer having a viscosity of 15,000 mPa·s at 25° C. and a vinyl content of about 8.0% by weight; Vinyl-terminated siloxane copolymer 2 is a dimethylvinyl-terminated dimethylmethylvinyl polysiloxane copolymer having a viscosity of 300 mPa·s at 25° C. and a vinyl content of about 1.15% by weight; Fumed silica is 300m 2 HDK® T30P pyrogenic silica (Wacker Chimie) with a BET surface area of 1.0 g / g; HMDZ is hexamethyldisilazane; MVD (methylvinyldiol) is a dimethylhydroxy-terminated polydimethylmethylvinylsiloxane having a viscosity of about 30 mPa·s at 25°C and a vinyl content of about 12.0% by weight. the platinum catalyst being a platinum catalyst in a solution of polydimethylsiloxane having about 5000 ppm platinum metal relative to the remainder of the composition; The inhibitor is methyl(tris(1,1-dimethyl-2-propynyloxy))silane; ZrAcAc masterbatch is zirconium acetylacetonate in a 50:50 masterbatch of vinyl terminated siloxane polymer; Silane 1 is 3-glycidoxypropyltrimethoxysilane.
[0135] Two skin layers were used in the examples. The formulations used in the following examples are shown in Table 4.
[0136] [Table 6]
[0137] SILASTIC™ LCF 8300 Skin is a two-component silicone system engineered for high strength and hardness for added abrasion resistance when coated onto fabrics, and is designed for use as a skin layer for synthetic silicone leather available from Dow Silicones Corporation (Midland Michigan USA). SILASTIC™ LCF 8500 Skin is a two-component silicone system designed for high strength and hardness for increased abrasion resistance when coated onto fabrics, and is designed for use as a skin layer for synthetic silicone leather available from Dow Silicones Corporation (Midland Michigan USA). SILASTIC™ LCF 8300 Skin and SILASTIC™ LCF 8500 Skin are designed to be blended together if desired.
[0138] Skin layer 1 is essentially the same as skin layer 2, except for the addition of an adhesion promoter.
[0139] The silicone binder layer utilized to adhere the fabric to the skin layer was SILASTIC™ LCF 8400 Binder, a two-component silicone system designed for high strength adhesion to textile substrates, commercially available from Dow Silicones Corporation (Midland Michigan USA).
[0140] A selection of Comparative Examples (C1-3) and Examples Ex.1-4 were then prepared such that the silicone binder layer (ii) was between the textile substrate (i) and the skin layer (iii), the skin layer (iii) was between the silicone binder layer (ii) and the silicone / polyurethane hybrid prepolymer-based coating layer (v), and the silicone / polyurethane hybrid prepolymer-based coating layer (v) was between the skin layer (iii) and the silicone topcoat (iv). The release paper used in all Examples was Type DE-73M available from Dai Nippon Printing Co.Ltd, and the silicone binder layer utilized to bond the fabric to the skin layer was SILASTIC™ LCF 8400, and other compositions used to make each of the composites of Comparative Examples 1-3 (C1-3) and Ex.1-4 are shown in Table 5 below.
[0141] [Table 7]
[0142] In each of Comparative Examples 1-3 and Examples 1-4, the two-part hydrosilylation curable silicone topcoat composition, the silicone / polyurethane hybrid prepolymer-based coating composition, the skin layer coating composition, and the Part A and Part B compositions of the silicone binder composition were mixed to produce the final composition of each layer. The resulting skin layer coating composition and silicone binder composition were degassed, and each silicone leather composite was prepared as follows:
[0143] The additional process steps carried out to obtain composite C.1 were as follows: 1) A silicone topcoat composition was coated onto a release paper and cured at 150° C. for 5 minutes to give a topcoat layer having an average dry coat thickness of about 13 μm. 2) The silicone skin layer composition was then applied onto the topcoat layer and then cured for 1.5 minutes at 120° C. The average dry coat thickness of the resulting skin layer was about 125 μm. 3) The adhesive layer composition was coated onto the skin layer, laminated to the fabric layer, and then cured for 3 minutes at 140° C. The average dry coat thickness of the adhesive layer was about 250 μm. 4) The release paper was then removed for this example.
[0144] The process followed to obtain composite C.2 was as follows: 1) The silicone / polyurethane hybrid prepolymer-based coating composition was coated onto a release paper and then cured for 3 minutes at 150° C. The average dry coat thickness of the resulting silicone / PU hybrid coating layer was about 20 μm. 2) The silicone skin layer composition was then applied onto the silicone / PU hybrid coating layer and cured for 1.5 minutes at 120° C. The average dry coat thickness of the resulting skin layer was about 125 μm. 3) The adhesive layer composition was then coated onto the skin layer, then laminated to the fabric layer and cured for 3 minutes at 140° C. The average dry coat thickness of the resulting adhesive layer was about 250 μm. 5) The release paper was then removed for this example.
[0145] In each case, the additional process steps carried out to obtain Composite C.3 and Examples 1-4 were as follows: 1) The silicone / polyurethane hybrid prepolymer coating composition was applied onto a release paper and cured for 3 minutes at 150° C. The average dry coat thickness of the silicone / polyurethane hybrid prepolymer coating layer was about 20 μm. 2) The silicone skin layer composition was then applied onto the silicone / polyurethane hybrid prepolymer-based coating layer and then cured for 1.5 minutes at 120° C. The average dry coat thickness of the resulting skin layer was about 125 μm. 3) The adhesive composition was then coated onto the skin layer, then laminated to the fabric layer, and then cured for 3 minutes at 140° C. The average dry coat thickness of the resulting adhesive layer was about 250 μm. 4) The release paper is removed from the silicone / polyurethane hybrid prepolymer coating layer, and a silicone topcoat composition is applied onto the silicone / polyurethane hybrid prepolymer coating layer and cured for 5 minutes at 150° C. The average dry coat thickness of the silicone topcoat in each example was about 13 μm.
[0146] The abrasion resistance of each of the obtained silicone leather composite materials was tested using a Gakushin Model: GT-7020 manufactured by GOODTECHWILL Testing Machines Co., Ltd.
[0147] The silicone leather composites were cut into 10x100mm rectangles and then attached to the weighted test head of a Gakushin Model: GT-7020 using double-sided tape. The abrasive action was provided by a piece of cotton abrasive cloth (JIS L3102 6# 30mmx250mm) placed on the moving curved platen of the Gakushin instrument. The platen moved back and forth at 30 cycles / min, and the total weight of each head was 1kg. The test was stopped every 2000 cycles to observe the effect on the surface of the leather composites, as shown in Tables 6a and 6b below.
[0148] [Table 8]
[0149] Comparative Example 3 was not tested because the silicone topcoat could be rubbed off even with a finger due to poor adhesion to the silicone / polyurethane hybrid prepolymer-based coating layer (v). Ex. 1-4 were also analyzed after the abrasion test and were determined to pass the test. Details of the observations are provided in Table 6b below.
[0150] [Table 9]
[0151] Each of the silicone leather composite materials (Ex.1 to Ex.4) had no significant change in surface texture after passing the Gakushin test for the two-component hydrosilylation-curable silicone topcoat coating, and retained a soft feel.
[0152] A second batch of examples utilized the composition of Example 1 for the purposes of evaluating the best method for the process herein.
[0153] Comparative Example 4: 1) A silicone / polyurethane hybrid prepolymer coating composition (SPHPT1) was applied onto a release paper and then cured by heating for 8 minutes at 120° C. The thickness of the resulting cured silicone / polyurethane hybrid prepolymer coating layer was approximately 70 μm. 2) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 130° C. The average thickness of the dried skin layer was about 140 μm. 3) The silicone binder composition was then coated onto the skin layer, which was then laminated to a fabric backing layer and cured for 3 minutes at 150° C. The average thickness of the dried binder layer was about 250 μm. 4) Finally, the release paper was removed and a two-part hydrosilylation-curable silicone topcoat was applied onto the cured silicone / polyurethane hybrid prepolymer coating layer and cured at 150°C for 5 minutes. The average thickness of the cured, dried silicone topcoat is about 10 μm.
[0154] Comparative Example 5: 1) The silicone / polyurethane hybrid prepolymer coating composition SPHPT1 was applied onto a release paper and then cured by heating for 3 minutes at 150° C. The thickness of the resulting cured silicone / polyurethane hybrid prepolymer coating layer was about 20 μm. 2) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 120° C. The average thickness of the cured dry skin layer was about 125 μm. 3) The silicone binder composition was then coated onto the skin layer, then laminated to a fabric backing layer, and then cured for 3 minutes at 140° C. The average thickness of the dried silicone binder layer was about 250 μm. 4) Finally, the release paper was removed and a two-part hydrosilylation-curable silicone topcoat was applied. The release paper was removed and the two-part hydrosilylation-curable silicone topcoat was coated onto the cured silicone / polyurethane hybrid prepolymer coating layer and cured at 150°C for 5 minutes. The average thickness of the cured, dried silicone topcoat layer was approximately 50 μm.
[0155] Comparative Example 6: 1) The silicone / polyurethane hybrid prepolymer coating composition SPHPT1 was applied onto a release paper and then cured by heating for 3 minutes at 150° C. The thickness of the resulting cured silicone / polyurethane hybrid prepolymer coating layer was about 20 μm. 2) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 120° C. The average thickness of the cured dry skin layer was about 20 μm. 3) The silicone binder composition was then coated onto the skin layer, then laminated to a fabric backing layer, and then cured for 3 minutes at 140° C. The average thickness of the dried silicone binder layer was about 250 μm. 4) Finally, the release paper was removed and a two-part hydrosilylation-curable silicone topcoat was applied onto the cured silicone / polyurethane hybrid prepolymer coating layer and cured for 5 minutes at 150° C. The average thickness of the cured, dried silicone topcoat layer was about 13 μm.
[0156] Comparative Example 7: 1) A two-part hydrosilylation-curable silicone topcoat composition was applied onto a release paper and cured for 5 minutes at 150° C. The thickness of the cured, dried silicone topcoat layer was approximately 13 μm. 2) The silicone / polyurethane hybrid prepolymer coating composition SPHPT1 was applied onto the silicone topcoat layer and then cured by heating for 3 minutes at 150° C. The average thickness of the resulting cured silicone / polyurethane hybrid prepolymer coating layer was about 20 μm. 3) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 120° C. The thickness of the cured skin layer was about 140 μm. 4) The silicone binder composition was then coated onto the skin layer, then laminated to a fabric backing layer, and then cured for 3 minutes at 140° C. The average thickness of the dried silicone binder layer was about 250 μm. 5) Remove the release paper.
[0157] Example 5 1) The silicone / polyurethane hybrid prepolymer coating composition SPHPT1 was applied onto a release paper and then cured by heating, and the silicone / polyurethane hybrid prepolymer coating layer was applied onto the release paper and then cured by heating for 3 minutes at 150° C. The average thickness of the resulting cured, dried silicone / polyurethane hybrid prepolymer coating layer was about 20 μm. 2) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 120° C. The average thickness of the cured dry skin layer was about 125 μm. 3) The silicone binder composition was then coated onto the skin layer, then laminated to a fabric backing layer, and then cured for 3 minutes at 140° C. The average thickness of the dried silicone binder layer was about 250 μm. 4) Finally, the release paper was removed, and a two-part hydrosilylation-curable silicone topcoat composition was applied onto the cured silicone / polyurethane hybrid prepolymer coating layer and cured for 5 minutes at 150° C. The average thickness of the silicone topcoat layer was about 13 μm.
[0158] Example 6: 1) The silicone / polyurethane hybrid prepolymer coating composition SPHPT2 was applied onto a release paper and then cured by heating for 8 minutes at 120° C. The thickness of the resulting cured silicone / polyurethane hybrid prepolymer coating layer was about 30 μm. 2) Skin layer composition SL1 was then applied on top of the cured silicone / polyurethane hybrid prepolymer-based coating layer and cured for 1.5 minutes at 130° C. The average thickness of the cured dry skin layer was about 70 μm. 3) The silicone binder composition was then coated onto the skin layer, then laminated to a fabric backing layer, and then cured for 3 minutes at 150° C. The average thickness of the dried silicone binder layer was about 200 μm. 4) Finally, the release paper was removed, and a two-part hydrosilylation-curable silicone topcoat composition was applied onto the cured silicone / polyurethane hybrid prepolymer coating layer and cured for 5 minutes at 150° C. The thickness of the silicone topcoat layer was about 10 μm.
[0159] The six composites obtained were tested in the same manner as above, and found to have poor hand feel in Comparative Example 4, where the average dry coat thickness of the silicone / polyurethane hybrid prepolymer coating layer was thicker than the desired range. In Comparative Example 5, the average dry coat thickness of the silicone topcoat layer was greater than the specified upper limit, and the resulting composites had significant negative changes in gloss and texture. In Comparative Example 6, the average dry coat thickness of the skin layer was less than the required thickness, and the resulting composites were significantly damaged after 4000 cycles of the Gakushin test and were therefore deemed to have failed the Gakushin test. In Comparative Example 7, the silicone topcoat layer was applied directly onto the release paper as step 1 of the process. It was found that most of the silicone topcoat remained on the release paper and, as a result, remained on the paper, failing the Gakushin test. In contrast, Example 5 of the present invention was observed to retain a soft hand feel, with no significant change in surface texture after silicone topcoat coating, and passed the Gakushin test, and Example 6 of the present invention was also observed to retain a soft hand feel, with no significant change in surface texture after silicone topcoat coating, and passed the Gakushin test.
Claims
1. 1. A silicone leather composite material, comprising: (i) a textile support layer; and (ii) a silicone binder, the silicone binder being a cured product of a two-part hydrosilylation-curable silicone rubber composition designed to adhere to the textile support layer (i) and the skin layer (iii), the silicone binder having a Shore A hardness of 20 to 40 as measured in accordance with ASTM D2240; (iii) a silicone skin layer, the silicone skin layer being a cured product of a two-part hydrosilylation-curable silicone rubber composition containing an adhesion promoter, the silicone skin layer having a Shore A hardness of 50 or greater (≧) as measured according to ASTM D2240; and (iv) a silicone topcoat layer that is a cured product of a two-part hydrosilylation-curable silicone topcoat that includes an adhesion promoter; the silicone binder (ii) is adhered between the textile substrate (i) and the skin layer (iii), the skin layer (iii) being between the silicone binder layer (ii) and the silicone topcoat layer (iv); A silicone leather composite, characterized in that a silicone / polyurethane hybrid prepolymer-based coating layer (v) having an elastic modulus of 10 MPa or more, determined by calculating the elastic modulus using the initial linear portion of the load-elongation curve according to ASTM D882, is provided in said silicone leather composite between said silicone skin layer (iii) and said silicone topcoat layer (iv).
2. The silicone / polyurethane hybrid prepolymer coating layer (v) is a cured product of a silicone / polyurethane hybrid prepolymer coating composition, the composition comprising: (v) (a) a silicone / polyurethane hybrid prepolymer; (v)(b) an optional cured silicone elastomer powder; and (v)(c) any silicon-free inorganic particles and / or particulates selected from at least one of polymethyl methacrylate (PMMA), ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), or a polyurethane polymer; and (v)(d) a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (-Si-H) groups per molecule, present in an amount of 1% to 10% by weight of the composition. (v)(f) a polyether polyol having at least two hydroxyl groups per molecule and a hydroxyl number greater than 100 mg KOH / g as measured in accordance with ASTM D4274-11; (v) (g) a platinum group metal-based catalyst. The silicone leather composite material of claim 1 .
3. 3. The silicone leather composite of claim 2, wherein said silicone / polyurethane hybrid prepolymer based coating composition further comprises a polyurethane curing catalyst (v)(e).
4. 4. The silicone leather composite material according to claim 2 or 3, wherein said silicone / polyurethane hybrid prepolymer based coating composition contains one or both of: (v)(b) said cured silicone elastomer powder; and (v)(c) said silicon-free inorganic particles and / or microparticles selected from at least one of polymethyl methacrylate (PMMA), ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), or polyurethane polymer.
5. The silicone leather composite material according to any one of claims 1 to 4, wherein the average dry coat thickness of said silicone / polyurethane hybrid prepolymer based coating layer (v) is between 10 μm and 50 μm using the method disclosed herein.
6. the silicone topcoat layer (iv) being a cured product of a two-part hydrosilylation-curable silicone topcoat composition, the composition comprising: Component (iv)(a) one or more organopolysiloxane polymers having at least two unsaturated groups per molecule, the unsaturated groups being selected from alkenyl groups, alkynyl groups, or mixtures thereof, and having a viscosity of 100 to 500,000 mPa·s at 25° C.; Component (iv)(b) a silica reinforcing filler which is optionally hydrophobically treated; component (iv)(c) a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (—Si—H) groups per molecule; component (iv)(d) a hydrosilylation catalyst; Component (iv)(e) an adhesion promoter comprising zirconium acetylacetonate in an amount of 1 to 5 weight percent of the composition, 1,3,5-tris[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in an amount of 1 to 6% by weight of the composition, and / or one or more epoxy silanes of the formula: 【Chemistry 1】 In the formula, R 5 is an alkyl group having 1 to 6 carbon atoms, and R 6 is an alkoxy group having 1 to 6 carbons and z=0, 1 or 2, in combination with an epoxy silane, or mixtures thereof; component (iv)(f) an eco-solvent, and optionally Component (iv) (g) cured silicone powder. The silicone leather composite material according to any one of claims 1 to 5, comprising:
7. The silicone leather composite material according to any one of claims 1 to 6, wherein the one or more adhesion promoters in the two-part hydrosilylation-curable silicone rubber composition provided to produce the skin layer (iii) comprise at least one isocyanatoalkylsilane and / or one epoxysilane.
8. the average dry coat thickness of said silicone skin layer (iii) is from 70 μm to 200 μm; and / or The silicone leather composite according to any one of claims 1 to 7, wherein the average dry coat thickness of said two-part hydrosilylation curable silicone topcoat (iv) is between 5 and 20 μm, and / or the average dry coat thickness of said silicone / polyurethane hybrid prepolymer based coating layer (v) is between 10 μm and 50 μm.
9. A method for preparing a silicone leather composite material according to any one of claims 1 to 8, comprising the steps of: (a) coating a release paper with a layer of a silicone / polyurethane hybrid prepolymer-based coating composition and curing said composition to provide a silicone / polyurethane hybrid prepolymer-based coating layer (v); (b) applying a layer of a silicone skin composition onto the cured silicone / polyurethane hybrid prepolymer based coating layer (v) and curing the silicone skin composition to provide a silicone skin layer (iii); (c) applying a layer of a silicone binder composition onto the cured silicone skin layer (iii), applying a textile layer (i) onto the silicone binder composition, and curing and / or laminating the composition to form a silicone binder layer (ii) between the textile support layer (i) and the skin layer (iii); (d) removing the release paper from the cured silicone / polyurethane hybrid prepolymer based coating layer (v); (e) applying a layer of a two-part hydrosilylation-curable silicone topcoat composition over the cured silicone / polyurethane hybrid prepolymer based coating layer (v) and curing the two-part hydrosilylation-curable silicone topcoat composition to form a silicone topcoat layer (iv).
10. 10. The process of claim 9, wherein the silicone / polyurethane hybrid prepolymer based coating composition is cured at a temperature of 120° C. to 180° C. for 2 to 10 minutes to obtain an average dry coat thickness of 10 μm to 50 μm using the methods described herein.
11. 11. The process of claim 9 or 10, wherein the two-part hydrosilylation-curable silicone topcoat composition is cured at a temperature of from 130° C. to 160° C. for 2 to 8 minutes to form a silicone topcoat (v) having an average dry coat thickness of from 5 to 20 μm using the methods disclosed herein.
12. Use of a silicone / polyurethane hybrid prepolymer-based coating composition for improving the abrasion resistance in a silicone leather composite material according to any one of claims 1 to 8, the silicone / polyurethane hybrid prepolymer-based coating layer (v) having an elastic modulus of 10 MPa or more, determined by calculating the elastic modulus using the initial linear portion of the load-elongation curve according to ASTM D882.
13. The silicone / polyurethane hybrid prepolymer-based coating composition comprises: (v) (a) a silicone / polyurethane hybrid prepolymer; (v)(b) an optional cured silicone elastomer powder; and (v) (c) any silicon-free organic particles and / or particulates selected from at least one of polymethyl methacrylate (PMMA), ethylene-vinyl acetate copolymer (EVA), ethylene-acrylate copolymer (EAA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), or a polyurethane polymer; (v)(d) a polyorganosiloxane containing at least two, alternatively at least three silicon-bonded hydrogen (—Si—H) groups per molecule, present in an amount from 1% to 10% by weight of the composition; (v)(f) a polyether polyol having at least two hydroxyl groups per molecule and a hydroxyl number greater than 100 mg KOH / g as measured in accordance with ASTM D4274-11; (v) (g) a platinum group metal-based catalyst.
14. 13. The use of the silicone / polyurethane hybrid prepolymer coating composition according to claim 12, wherein said silicone / polyurethane hybrid prepolymer coating composition further comprises a polyurethane curing catalyst (v)(e).
15. Use of a layer of a silicone / polyurethane hybrid prepolymer-based coating layer (v) in a silicone / polyurethane composite leather material according to any one of claims 1 to 8 or prepared according to the method according to claim 8 in or for furniture, decoration, handbags, binders, luggage, clothing, phone covers, covers for electronic goods, book covers, footwear, automobile interiors, automobile seats, wearable devices, and / or medical beds / sheets.
Citation Information
Patent Citations
Organic silicon polycarbonate type polyurethane synthetic leather and preparation method thereof
CN112482048A
Liquid silicone rubber composition
JP2020526622A
Coating composition and its uses
WO2020233268A1
An abrasion resistant multi-layered composite
WO2021134193A1